Pendidikan Agama Islam Sebagai Landasan Filosofis Dalam Membentuk Karakter Manusia Di Era Society 5.0 - Ismail, Ismail; Arifin, Syamsul; Ishomuddin, Ishomuddin (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study explores the strategic role of Islamic Religious Education (IRE) as a philosophical foundation in shaping human character in the Society 5.0 era. Amid globalization and rapid technological advancement, religious values are often marginalized or distorted. This research aims to analyze Surah Al-Baqarah verse 129 as a foundation for developing a relevant and applicable IRE curriculum in modern times. The method used is library research, focusing on analyzing literature related to Islamic education, character development, and the integration of Islamic and general sciences. The findings highlight three key pillars emphasized in the verse: strengthening faith (aqidah), teaching the Qur’an and Sunnah, and purification of the soul. These components are essential in shaping morally upright and intellectually capable individuals. The study also reveals that technological integration, holistic approaches, and lifelong learning are critical strategies for addressing challenges in contemporary Islamic education. By adopting Surah Al-Baqarah:129 as a philosophical foundation, IRE can foster a generation that is ethical, tolerant, and globally competitive without losing its spiritual identity.